A comparative study of conceptual graph and concept map - Mohamad Rasli, Ruziana; Ahmad, Faudziah; Kamaruddin, Siti Sakira (Asian Research Publishing Network (ARPN), 2014)
The purpose of this paper is to compare two types of graphical models that are widely being used nowadays. The models are called conceptual graph and concept map.Although the names of these models are similar, however, the characteristics of each model are different.A number of 18 papers are compared and important elements for these models are discussed in these papers.This paper is divided into eight sub-topics.The output of this paper is the comparison of characteristics and usage of these two graphical models.In the last part of this paper, a conclusion of the models is made to give better view of it.